2022
DOI: 10.1186/s13690-022-00822-5
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of men involvement in family planning services use and associated factors in rural Ghana

Abstract: Background In low-and-middle income countries (LMICs) less attention is paid to men’s involvement in Family Planning (FP) programs where public health officials have advocated the involvement of men as a strategy for addressing the dismal performance of FP programs. The study assessed the involvement of men in FP use and the factors which promote or hinder the uptake of FP services among partners in a rural setting of northern Ghana. Methods A cros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 19 publications
1
1
0
Order By: Relevance
“…Thus, education is crucial to accelerate women empowerment for their health needs. This finding concurs with a study done by [ 34 36 ] who reported that socio cultural factors affect use of FP despite strong interest of individuals to use it because of low educational level and over believing in cultural norms.…”
Section: Discussionsupporting
confidence: 92%
“…Thus, education is crucial to accelerate women empowerment for their health needs. This finding concurs with a study done by [ 34 36 ] who reported that socio cultural factors affect use of FP despite strong interest of individuals to use it because of low educational level and over believing in cultural norms.…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies have reported that approximately 59% and 42% of men in rural Ethiopia and in pastoralist communities, respectively, are involved in family planning (10) , (11) . Furthermore, 48% of men in rural Ghana reportedly participate in family planning services (12) . Factors related to men’s participation in family planning include communication with their spouses concerning sexual and reproductive health, family planning, and agreement with family planning (10) , (11) .…”
Section: Introductionmentioning
confidence: 99%